Practical and professional ethics the primer of applied ethics [6v.] - Guha, Debashis (New Delhi Concept Publishing, 2009)
Contents: V.1-the priemer of applied ethics, V.2-Environmental ethics, V.3-Biomedical ethics, V.4-Educational ethics, V.5-Economic and business ethics, V.6 Socio-Political ethics
Keywords: Applied ethics